Experimental and Theoretical Investigations of Spectroscopic Properties of Clobazam - M.Prasath2, R. Arun Balaji3, S.Muthu1, (Recent Research in Science and Technology, 2011)
Ab initio and density functional theory methods have been employed to study the vibrational (IR) spectrum, molecular geometry, and chemical shifts of clobazam (CLB). Experimental studies were conducted on these parameters, including FTIR, FTRaman and 1H- and 13C NMR spectroscopy. The FTIR and FTRaman spectra of Clobazam have been recorded in the region 4000-400cm-1 and 3500-100 cm-1respectively. On the basis of the comparison between calculated and experimental results and the comparison with related molecules, assignments of fundamental vibrational modes are examined. A detailed interpretation of the infrared spectrum of CLB is reported.Ã‚Â Moreover, the complete assignment of 1H- and 13C-NMR signals was achieved using DFT/GIAO calculated isotropic magnetic shielding at the B3LYP/6-31G(d) basis set. Theoretical values were compared to the experimental dataÃ¢â‚¬â„¢s.